2022
DOI: 10.3390/jcm11071897
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Phosphate Concentrations and Hospital Mortality in Critically Ill Patients Receiving Mechanical Ventilation

Abstract: Phosphate concentrations change continuously throughout hospitalization; however, it is unclear which available phosphate measures are most clinically important for predicting hospital mortality. Therefore, we investigated phosphate concentrations in association with hospital mortality following admission to the intensive care unit. We retrospectively enrolled all adult patients receiving mechanical ventilation. Phosphate concentrations were divided into three categories: initially measured phosphate (iP); max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The prediction of mechanical ventilation duration could affect both clinical management and intensive care resource utilization. Additionally, comorbidities, such as the presence of chronic respiratory disease, heart failure, cerebrovascular diseases, malnutrition, and end-stage renal failure, affected the duration of mechanical ventilation and the final outcome [ 8 , 9 , 10 ]. Unfortunately, an accurate prediction of mechanical ventilation is quite difficult for critical care physicians according to clinical data at admission.…”
mentioning
confidence: 99%
“…The prediction of mechanical ventilation duration could affect both clinical management and intensive care resource utilization. Additionally, comorbidities, such as the presence of chronic respiratory disease, heart failure, cerebrovascular diseases, malnutrition, and end-stage renal failure, affected the duration of mechanical ventilation and the final outcome [ 8 , 9 , 10 ]. Unfortunately, an accurate prediction of mechanical ventilation is quite difficult for critical care physicians according to clinical data at admission.…”
mentioning
confidence: 99%
“…11,16 5 | CONCLUSIONSIn this multicenter cohort study, we found that 50%, 56%, and 91% of the patients presented with abnormal serum magnesium, phosphate, and zinc at ICU admission, and that most patients experienced low serum levels during ICU stay. Patients often received supplementation of magnesium, phosphate, and zinc, and experiencing both low and high serum levels during ICU stay was not uncommon.…”
mentioning
confidence: 74%
“…Therefore, these findings should be interpreted with great caution, and so should the associations between hypermagnesemia and longer time to successful extubation, hyperphosphatemia and shorter duration of mechanical ventilation, hypozincemia and increased mortality, and finally, the associations between high serum levels of magnesium or phosphate and mortality, although increased mortality is in line with most previous findings. 11,12,16,18,20…”
Section: Patient Outcomesmentioning
confidence: 99%
See 2 more Smart Citations